CYLINDRICAL AND CONICAL SURFACES: SECOND-ORDER SURFACES AND THEIR TYPES - Boboqulova Durdona Sanjar qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This paper examines cylindrical and conical surfaces as fundamental types of second-order (quadratic) surfaces in three-dimensional space. These surfaces play a significant role in mathematical modeling, architectural design, mechanical engineering, and computer graphics. The study explores their definitions, general equations, geometric properties, and practical applications. A comparative analysis of cylindrical and conical surfaces within the context of quadratic surfaces is presented, along with visual interpretation and classification based on their algebraic forms.